RT-PCR–Based Detection of Bone Marrow Involvement in Ewing Sarcoma: Diagnostic Validity and Prognostic Relevance - Pham, Thanh; Ranft, Andreas; Rechl, Victor; Jabar, Susanne; Hartmann, Wolfgang; Falkenberg, Kim; Jürgens, Heribert; Graf, Norbert; Keßler, Torsten; Metzler, Markus; Klingebiel, Thomas; Simon, Thorsten; et al. (Pediatric Blood & Cancer, 2026)
Background: In Ewing sarcoma (EwS), metastases, including those to bone marrow (BM), are the main factors influencing prognosis. Although reverse transcription polymerase chain reaction (RT-PCR) offers greater sensitivity, the current EWING protocol defines BM metastases solely using light microscopic detection. However, the prognostic relevance of BM metastases remains unclear. We evaluated the diagnostic validity and prognostic relevance of RT-PCR for detecting BM involvement in EwS. Procedure: We retrospectively analyzed 316 patients from the EWING 2008 trial (NCT00987636), stratified by BM status: Group 1 (RT-PCR−/microscopy−), Group 2 (RT-PCR+/microscopy−), and Group 3 (RT-PCR+/microscopy+). Event-free survival (EFS) and overall survival (OS) were assessed using Kaplan–Meier and Cox regression analyses, including subgroup analyses by metastatic status at diagnosis. Results: Kaplan–Meier analysis of EFS showed relevant differences (overall [Group 2 vs Group 1: HR = 2.27; 95% CI: 1.33–3.87, p = 0.003; Group 3 vs Group 1: HR = 2.98; 95% CI: 0.94–9.45, p = 0.064], localized disease [Group 2 vs Group 1: HR = 1.30; 95% CI: 0.47–3.62, p = 0.61], metastatic disease [Group 2 vs Group 1: HR = 2.56; 95% CI: 1.32–4.96, p = 0.006; Group 3 vs Group 1: HR = 1.85; 95% CI: 0.57–6.01, p = 0.307]). OS analysis showed comparable results. Conclusions: The validity of RT-PCR is at least comparable to that of microscopy, and it additionally detects submicroscopic BM involvement, supporting its use as a standalone method for initial staging. The prognostic implications of BM assessment remain relevant.
CRIS-Team Scopus Importer:2026-02-06
Keywords: bone marrow involvement; bone marrow metastases; Ewing sarcoma; molecular diagnostics; prognosis; RT-PCR